A new species of Acanthormius (Braconidae: Lysiterminae) reared as a gregarious parasitoid of psychid caterpillar (Lepidoptera: Psychidae) from India - Gupta, Ankita; Quicke, Donald L. J. (Zootaxa, 2018)
Acanthormius indicus Gupta & Quicke sp. nov. is described and illustrated. It is a gregarious larval parasitoid of an unidentified bagworm moth caterpillar (Lepidoptera: Psychidae) from southern India. The biology and host associations of members of subfamily Lysiterminae are also discussed.